2014
DOI: 10.3892/ol.2014.2606
|View full text |Cite
|
Sign up to set email alerts
|

Bmi-1 induces radioresistance by suppressing senescence in human U87 glioma cells

Abstract: Radiotherapy is the main locoregional control modality for a number of types of malignant tumors, including glioblastoma. However, radiotherapy fails to prevent recurrence in numerous patients due to the intrinsic radioresistance of cancer cells. Cell senescence is significant in tumor suppressor mechanisms and is closely associated with the radioresistance of cancer cells. Bmi-1 has been proposed to be an oncogene that can induce anti-senescence in tumor cells. The present study investigated the response of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Cell senescence is characterized by an irreversible cell cycle arrest in G 0 /G 1 phase. In our previous study, in the 6 and 8 Gy groups following 72 h exposure to radiation, the number of senescent cells was markedly increased; however, the number of cells in G 0 /G 1 phase was markedly decreased (17). These results suggest that U-87 MG glioma cells exhibit cellular senescence evasion.…”
Section: Growth Of U-87 Mg Glioma Cells Following X-ray Exposurementioning
confidence: 76%
See 4 more Smart Citations
“…Cell senescence is characterized by an irreversible cell cycle arrest in G 0 /G 1 phase. In our previous study, in the 6 and 8 Gy groups following 72 h exposure to radiation, the number of senescent cells was markedly increased; however, the number of cells in G 0 /G 1 phase was markedly decreased (17). These results suggest that U-87 MG glioma cells exhibit cellular senescence evasion.…”
Section: Growth Of U-87 Mg Glioma Cells Following X-ray Exposurementioning
confidence: 76%
“…Furthermore, miRNA-23a is upregulated in glioma and promotes the invasion of glioma cells (16). Our previous study investigated the role of BMI1 polycomb ring finger oncogene (Bmi-1) in the response of U-87 MG cells to radiation exposure (17). The results indicated that miRNA-128a was able to bind to the 3'-UTR of Bmi-1 in order to suppress its expression.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations